The Reform of the Financial Information Authority and the Institute for the Works of Religion - ROMANKO, AGNIESZKA (Prawo Kanoniczne, 2017)
The author analyzes the reform of the Pope Francis in the Holy See and Vatican City State. At the beginning the Pope Francis established three organs helping him in the reform: Council of Cardinals, Papal Commission for the Reference on the Institute for Works of Religion, Pontifical Commission for Reference on the Organization of the Economic-Administrative Structure of the Holy See. Then the author describes the changes in the Financial Information Authority – establishment the Financial Security Committee and approving the new statute of the Authority – and in the Institute for the Works of Religion.